The Effect of Community Engagement Activities on Students’ Awareness of Veterans - Canaslan, Ayten; Sönmez, Azmi; Özkütük, Yarkin (Technium Social Sciences Journal, 2025)
This study aims to determine the effect of community engagement activities on students’ awareness of veterans. A phenomenological design, one of the qualitative research methods, was utilized in the study. Data was obtained through a semi-structured interview form, which was administered to the study group before and after the community engagement activities. The participants included a total of forty secondary school students, comprised of twenty males and twenty females, studying in the center of Ankara, Türkiye. The study examined students’ perceptions of the concept of veterans, the opportunities provided to veterans by the state, and the adequacy of these opportunities. Additionally, students’ perceptions regarding the initial intervention and treatment process for veterans after injury, society’s perspective on veterans, and veterans’ views on their experiences during the adaptation process to life and society were also explored. Furthermore, the knowledge levels of society about activities aimed at increasing awareness of veterans and their experiences, as well as perceptions of what can be done to aid veterans’ adaptation to life and society, were examined and compared separately before and after the community engagement activities. Overall, the findings indicated that community engagement activities positively impacted students’ awareness levels regarding veterans, with a notable increase in awareness linked to veterans’ experiences during their adaptation to life and society.